National Evaluation of the Troubled Families Programme: National Impact Study Report. Findings from the Analysis of National Administrative Data and local data on programme participation /: National Impact Study Report. Findings from the Analysis of National Administrative Data and local data on programme participation. (2016) - Bewley, Helen; George, Anitha; Rienzi, Cinzia; Portes, Jonathan
No abstract available